Correlations towards prediction of petroleum fraction viscosities: a semi-theoretical approach - (:unkn) unknown (ELSEVIER SCI LTD, 2000)
A new semi-theoretical method based on Enskog's hard sphere theory for dense fluids and the principle of corresponding states is presented for predicting viscosity of petroleum fractions (C-5-C-15) at 40 degrees C under atmospheric pressure. Viscosities, densities, normal boiling points and quantitative hydrocarbon analyses of 42 petroleum fractions were experimentally determined. The critical properties and the average molecular weights of the petroleum fractions were calculated by the Riazi Daubert equation. The predictions were compared with experimental data. Satisfactory results were obtained. The average error of the 42 petroleum fractions could be decreased to below 3.4% utilising only density and average boiling point as input parameters. The addition of hydrocarbon group weight fractions as additional input parameters decrease the average error to around 2.6%. When acyclic rich and cyclic rich samples are handled separately, the average errors are below 2%. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: semi-theoretical viscosity prediction method; petroleum fractions; hydrocarbon analyses; CRUDE OILS; MIXTURES